THE EFFECT OF FARTLEK WORKOUTS ON DEVELOPING SOME PHYSICAL ABILITIES AND PASS THE PHYSICAL FITNESS TESTS OF THE REFEREES OF THE THIRD DIVISION IN FOOTBALL (Neo Scientific Peer Reviewed Journal, 2023)
The study aims to prepare special workouts in the style of fartlek to develop some physical abilities and pass the physical fitness tests for the referees of the third degree of football. It identifies the impact of workouts for the style of fartlek in developing some physical abilities that enable passing the physical fitness tests for the referees of the third degree in football. The researcher used the experimental approach to suit the nature of the research. The research community are the referees of the third degree in Kirkuk football, which numbered (48) referees and 30 (62.5%) of the referee were selected and divided into two control and experimental groups. Each group consisted of (12) referee excluding (6) referees from the experiment for their participation in exploratory experiments. the researcher used statistical means: arithmetic mean, standard deviation, median, torsion coefficient, simple correlation coefficient (Pearson), T-test for the relevant samples.